2019
DOI: 10.1021/acs.chemmater.9b02973
|View full text |Cite
|
Sign up to set email alerts
|

Tunable and Stable White Light Emission in Bi3+-Alloyed Cs2AgInCl6 Double Perovskite Nanocrystals

Abstract: Lead-free double perovskite nanocrystals (NCs) of Cs2AgIn1–x Bi x Cl6 (x = 0, 0.05, 0.15, 0.3, 0.6, and 1) were synthesized with control over the size distribution. Detailed structural studies were carried out on the resulting double perovskite NCs to confirm the alloying and structural modification. Alloying of Bi leads to change in optical properties, such as the band gap, and enhancement in oscillator strength of first excitonic transition and the white light emission (WLE) properties. The band gap of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
147
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(153 citation statements)
references
References 38 publications
5
147
0
1
Order By: Relevance
“…The variation of lattice parameters as a function of Bi doping tallied with the theoretical Vegard's law line well, indicating an uniform cation distribution. [ 104 ] The volume of the Cs 2 AgIn 1‐ x Bi x Cl 6 unit cell expands from 1151 to 1250 Å 3 when Bi 3+ totally substitutes In 3+ . The linear increase between lattice parameters and substitution concentrations indicates solid‐solution behavior with dopants randomly distributed at B sites.…”
Section: Structural Diversity Of Hdpsmentioning
confidence: 99%
See 1 more Smart Citation
“…The variation of lattice parameters as a function of Bi doping tallied with the theoretical Vegard's law line well, indicating an uniform cation distribution. [ 104 ] The volume of the Cs 2 AgIn 1‐ x Bi x Cl 6 unit cell expands from 1151 to 1250 Å 3 when Bi 3+ totally substitutes In 3+ . The linear increase between lattice parameters and substitution concentrations indicates solid‐solution behavior with dopants randomly distributed at B sites.…”
Section: Structural Diversity Of Hdpsmentioning
confidence: 99%
“…(c) Reproduced with permission. [ 104 ] Copyright 2020, American Chemical Society. (d,e) Reproduced with permission.…”
Section: Optical Properties Of Hdpsmentioning
confidence: 99%
“…Bulk TlBr also has a parity‐forbidden indirect transition at 2.6–2.7 eV, but there is no evidence of this feature in the absorbance spectra of the nanocrystals. For the the Tl 2 AgBr 3 nanocrystals, an extrapolation of the linear region of the Kubelka Munk function in Figure B reveals an indirect bandgap of 3.1 eV . There is also an Urbach tail extending to longer wavelength, which could indicate the presence of silver‐thallium antisite defects.…”
Section: Resultsmentioning
confidence: 96%
“…Manna et al showed that Cs 2 AgIn 0.833 Bi 0.167 Cl 6 had a high PLQY of up to 39%, which provided an important reference for the study of the luminescence mechanism of these materials. [ 96 ]…”
Section: Recent Progress In Perovskite Materials For Wledsmentioning
confidence: 99%
“…Manna et al showed that Cs 2 AgIn 0.833 Bi 0.167 Cl 6 had a high PLQY of up to 39%, which provided an important reference for the study of the luminescence mechanism of these materials. [96] Another effective strategy for the construction of lead-free perovskite materials is through the use of low-toxic elements such as antimony (Sb), tin (Sn), and bismuth (Bi) as lead substitutes. [97] In 2018, Tan et al prepared a Bi-doped lead-free inorganic perovskite Cs 2 SnCl 6 :Bi with high-efficiency blue light emission at 455 nm, and a quantum yield close to 80%.…”
Section: Lead-free Perovskite Materials For Wledmentioning
confidence: 99%